(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bioplastics provide voluminous rewards compared to conventional plastics derived from fossil fuels. Among the principal advantages of bioplastics are the following: Bioplastics are made from plant-based materials such as potato starch, sugarcane, maize, and other renewable resources. When comparing standard plastics to bioplastics, the former often have a lower carbon footprint. Biodegradable or compostable, bioplastics are designed to disintegrate over time into their constituent parts. This might help reduce environmental contamination and the long-term impacts of plastic waste. A class of biopolymers known as polyhydroxybutyrates (PHBs) is produced by different microbial species. PHB is not made of petroleum-based chemicals, like produced plastics, and is recyclable and biocompatible. PHBs have innovative applications in packaging, nanotechnology, medicine, and agriculture, among other areas. PHB is produced using a range of feed sources, such as dairy waste, food industry waste, and agricultural waste. Right now, PHB characterization and production from Palmyra haustorium which is an underutilised carbohydrate containing substrate. The ability of Bacillus megaterium to synthesize PHB under the right circumstances and with the right amount of nutrients. In order to increase the cellulose content by 84.20 percent, the physical and chemical characteristics of the raw substrate Palmyra haustorium were investigated. The optimal conditions for PHB formation are 35°C and pH 7. The highest temperature, as determined by thermo gravimetric analysis, is 259.8°C. The thermal deterioration range is 287°C, while the melting temperature of the DTA peak is 256°C. hOne of an affordable substrate that yields more PHB is Palmyra haustorium